Fiscal Disparities and Local Own-Source Revenue Across Indonesian Provinces: Contribution, Growth, Elasticity, and Trends - Muhammad Rizki Rahmadani Rizki; Diana Sapha; Asri Diana; Putri Bintusy Syathi; Anita Faiziah (Jurnal Investasi Islam, 2026)
This study analyzes the characteristics and disparities of Local Own-Source Revenue (PAD) across Indonesian provinces during 2015–2024 and their implications for local fiscal autonomy. Secondary data from the Directorate General of Fiscal Balance (DJPK) cover 34 provinces (340 province-year observations per PAD component) and are examined descriptively through contribution ratios, growth ratios, elasticity, and trend analysis. Local taxes dominate PAD, averaging above 50 percent in nearly all provinces and exceeding 75 percent in DKI Jakarta (86.3 percent), Banten (82.9 percent), Bali (76.6 percent), and West Java (75.1 percent), whereas Aceh reaches only 36.6 percent owing to its reliance on other legitimate local revenue. Fiscal disparities are wide: the highest provincial PAD (West Java, IDR 43.1 trillion) is roughly 54 times the lowest (West Sulawesi, IDR 0.8 trillion), and the three Java provinces account for about 43 percent of national PAD. PAD growth fluctuated, declining in 2020 due to the pandemic before recovering, while local-tax elasticity stays closest to unity and non-tax components remain highly volatile. The study contributes the first comprehensive national-level comparative mapping of PAD, moving beyond the prevailing single-region case studies, by linking structure, growth, elasticity, and trends within one framework. The findings imply the need for asymmetric fiscal policy toward low-capacity regions and diversification of non-tax revenue, particularly strengthening regional enterprises (BUMD), to build sustainable fiscal autonomy.